Influence of Electrode Material and EDM Parameters on Electrode Wear of AISI H13 Steel - Mostafa Adel Abdullah; Nareen Hafidh Obaeed; Aseil Mohammed Radhi; Hiba Adil Ahmed (Wasit Journal of Engineering Sciences)
Abstract: Electrical discharge machining (EDM) is a non-traditional process that uses the electrical spark discharge to machine electrically conducting materials for geometrically complex shapes or hard materials. In the current work, cupper and brass were used as the electrode material, and AISI H13 steel as the workpiece. Different input parameters were investigated namely: 20, 30, 40 A current, 50, 100, 150 μs pulse on time, and 1, 3, 6 mm gap. The workpiece thickness was fixed to 4 mm and the pulse off time was 25 μs. All EDM experiments were carried out in diesel oil and the voltage was 140 V. The results showed that the electrode wear decreased with increasing the pulse on time and gap and increased with increasing current for copper and brass electrode. The optimal conditions for minimum tool wear were: pulse on time 150 μs, current 20 A, and gap 6 mm for copper and brass electrodes. Electrode wear is minimum for copper at all parameter values compared to brass electrode.